Pengaruh Audit Tenure dan Fee Audit terhadap Kualitas Audit - Ina Nikmatul Chasanah; Zafirah Nur Sabrina; Cindy Eka Makhsunnah; Allisa Laily Aziza; Omi Pramiana (MARGIN ECO, 2022)
This study was conducted to test the effect of Audit Tenure and Fee Audit variables on Audit Quality. This research is a quantitative study. The population is taken from mining sector companies listed on the Indonesia Stock Exchange (IDX) from the period 2018 to 2021 which amounted to 71 companies. The sample in this study was 17 companies selected using the purposive sampling method. Data obtained a sample of 17 companies with a total sample of 68. The analysis technique used is logistic regression analysis with a significance level of 5%. The results of this study show that (1) Audit Tenure has a significant positive effect on Audit Quality, and (2) Audit Fee does not have a significant effect on Audit Quality.